Strātījiyyatu Ta’allumi al Lughati al ‘Arabiyyati li Tarqiyyati Qudrati Mahārati al Kitābati Laday al Talāmīżi bi Al Madrasati al ‘Āliyyati al Islāmiyyati al Ḥukūmiyyati bi Riyāwi - Prihartini, Yogia; Wahyudi, Hakmi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
This research is a qualitative research with the type of case study, namely accurate research on community unity within a certain period of time. This unit is located at the Riau State Islamic High School. The research tools used were socialist observations, interviews, and documents. In order for the data in this study to be correct, the researcher carried out: continuous monitoring, triangulation, looking for various problems to confirm it, reviewing back to the source, discussing it with those who were qualified, and checking field notes. The results of this study include the application of Arabic learning strategies to improve students' writing skills at Madrasah Aliyah Negeri Riau, meaning that teachers teach Arabic through sermons. The obstacles faced by teachers in implementing Arabic learning strategies to improve students' writing skills at Islamic Senior High School Pekanbaru Riau, among others: difficulty in Arabic grammar, difficulty in spelling Arabic. improve students' writing skills at Islamic Senior High School Pekanbaru Riau, among others as follows: Teachers use colored cards written in vocabulary to memorize, and teachers use pictures to tell stories in Arabic. Few of them understand the teaching of the Arabic language that the teacher gave in the class, especially for writing. The teacher has explained many times but they do not understand, and some of them grow when teaching the Arabic language because the teacher uses the non-directive method to promote the students' interest, and some of them joke when teaching Arabic because the Arabic language It is very difficult and that is why the teacher did not practice the exercises, and some of them get bored when teaching the Arabic language, and some of them did not graduate from the Islamic religious school and did not learn the Arabic language lesson before it, and if the teacher ordered them to write, they could not also.